'We didn't have a clue': Family caregivers' experiences of the communication of a diagnosis of schizophrenia. (February 2015) - Outram, Sue; Harris, Gillian; Kelly, Brian; Bylund, Carma L; Cohen, Martin; Landa, Yulia; Levin, Tomer; Sandhu, Harsimrat; Vamos, Marina; Loughland, Carmel
Background: Despite widespread acceptance of the principle that patients should be informed about their diagnosis, many clinicians are reluctant to provide a diagnosis of schizophrenia. This study examines family caregivers' experiences of the communication of a schizophrenia diagnosis and related information. Methods: A generic qualitative methodological approach was used. In all, 13 family caregivers were recruited in regional New South Wales, Australia. Semi-structured interviews were used to explore their experiences and perceptions of discussing the diagnosis, prognosis and treatment of schizophrenia with mental health professionals. Interviews were recorded, transcribed, codes generated and thematic analysis undertaken. Results: Family caregivers described long and difficult pathways to being given a diagnosis, haphazard means of finding out the diagnosis, high unmet needs for information, exclusion from the medical care process and problematic communication and general interactions with mental health clinicians. Caregivers were unanimous about the importance of receiving a timely diagnosis, for them and their relative with schizophrenia. Conclusion: Family caregivers are an integral part of the mental health-care system, and they should be included early in discussions of diagnosis and treatment of a person with schizophrenia. Their perspectives on communicating a diagnosis of schizophrenia provide important information for communication skills training of psychiatrists and other mental health professionals.